PKM : Pelatihan Inovasi Produk Madu Hutan Sumedang Yang Higenis Dan Modern - Dian Ade Kurnia; Gifthera Dwilestari; Mulyawan; Salwa Wulan Suci; Nurul Hidayah (CV. Multi Kreasi Media, 2024)
This report highlights the importance of improving the quality of forest honey products in Sumedang to meet hygienic and modern standards. The main issue is that traditional honey production practices do not meet cleanliness standards, hindering the product's competitiveness in the market. Objective: The goal of this activity is to educate and train forest honey entrepreneurs on innovative techniques that enhance the production process to be more hygienic and in line with modern standards. Methods: The implementation methods include providing education on cleanliness practices, training on more efficient and safe processing techniques, and guidance on the application of the latest technology. Results: The program results show a significant improvement in the quality of honey products, with the produced honey now meeting higher cleanliness standards and achieving better market competitiveness.